Breast cancer: 20-year evolution of the epidemiological and clinical profile in a reference cancer center - Mansani, Fabio Postiglione; Santos, Gabriel Wesley Barbosa dos; Ribas, Luiz Roberto Cavassola (Mastology, 2026)
Objective: To evaluate the epidemiological profile of female patients diagnosed with breast cancer between 2003 and 2023 at the Instituto Sul Paranaense de Oncologia in Ponta Grossa, Paraná. Methods: Data were collected from electronic medical records using a partially structured spreadsheet, followed by statistical analysis conducted with R software. Results: During the study period, 3,115 patients were diagnosed with breast cancer in this institution. The average age at diagnosis was 56.23 years, with slight variations over the analyzed period. The age group most affected was 51–65 years (38.39%), preceded by the 41–50 age group (24.78%). The most prevalent histological type was invasive ductal carcinoma (81.22%), then by ductal carcinoma in situ (7.51%), and lobular carcinoma (7.32%). The study identified a statistically significant difference in clinical stages at diagnosis between patients treated in the public and private healthcare systems. In advanced stages, such as stage III, 34.91% of patients in the Brazilian Unified Health System (SUS) were diagnosed at this stage, compared to only 18.66% in the private system. Similarly, in stage IV, the metastatic phase of the disease, 12.36% of patients were diagnosed in SUS, compared to 5.75% in the private healthcare system, with statistically significant differences between the two groups. Conclusion: The epidemiological profile of patients was consistent with the literature, including the distribution of histological types of breast cancer. No increase in cases among younger patients (≤40 years) was observed. Additionally, a significant difference in clinical stages at diagnosis was identified between public and private healthcare systems, reinforcing previous findings that patients in the public system are often diagnosed at more advanced stages, leading to worse clinical outcomes.